2017
DOI: 10.1080/13651501.2017.1381268
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of antipsychotic induced movement disorders in a tertiary care teaching hospital in India – a cross-sectional study

Abstract: The higher use of atypical antipsychotics had reduced the occurrence of movement disorders in our setup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Contrary to this, another study reported dose as the most common reason for OLDP [36]. The OLDP patterns in our study revealed a higher off-label use of benzodiazepines which is not parallel to other studies [2,37]. This might be due to a difference in morbidity pattern, as in our setting, the patients are commonly presenting with depression and schizophrenia, for which psychiatrists prescribed longer use of benzodiazepines to treat insomnia and decrease aggressive symptoms [38].…”
Section: Discussioncontrasting
confidence: 97%
“…Contrary to this, another study reported dose as the most common reason for OLDP [36]. The OLDP patterns in our study revealed a higher off-label use of benzodiazepines which is not parallel to other studies [2,37]. This might be due to a difference in morbidity pattern, as in our setting, the patients are commonly presenting with depression and schizophrenia, for which psychiatrists prescribed longer use of benzodiazepines to treat insomnia and decrease aggressive symptoms [38].…”
Section: Discussioncontrasting
confidence: 97%
“…Regarding the geographical distribution, the review included six studies from Europe [4,[25][26][27][28][29], five studies from Asia [30][31][32][33][34], two studies from Africa [35,36], one study from South America [37], and one study from North America [38]. Thirteen of these studies had employed cross-sectional design [4,26,[28][29][30][31][33][34][35][36][37] with two of which being a retrospective chart review [25,32] and the remaining two studies had employed cohort design [27,38]. The sample size of individual studies ranged from 28 [29] to 164,417 [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample size of individual studies ranged from 28 [29] to 164,417 [38]. Thirteen studies were conducted in hospital settings [4,[26][27][28][29][30][31][33][34][35][36][37][38] whereas two studies were conducted at rehabilitation centers [25,32]. Majority of studies were conducted on adult patients with schizophrenic or schizoaffective disorders whereas the rest studies were conducted on non-specific psychotic patients, acute psychotic patients with substance use disorder, and patients with severe mental illness.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most potent molecules that bind to the alpha-adrenergic receptors are clozapine, iloperidone, and risperidone. Clozapine, olanzapine, and quetiapine also bind to muscarinic cholinergic receptors [7,8]. The less common incidence of extrapyramidal side effects made the atypical antipsychotics very popular among psychiatrists [9].…”
Section: Introductionmentioning
confidence: 99%